Prinsip Insaniyah Dalam Kebijakan Hukum Pidana Di Indonesia (Studi Terhadap Undang-Undang Nomor 23 Tahun 2004 Tentang Penghapusan KDRT) - Mawindi, Dwi Satriani Begi, Kuswardani, S.H., M.Hum, Hartanto, S.H, M.Hum (2015)
Formulation insaniyah principle in criminal law policy in Indonesia has devined in Act No. 23 of 2004 on the Elimination of Domestic Violence which became one of the juridical instrument as part of government policy to create a social order that respects human rights (human rights) and the protection of the use of violence . Human rights protections spared from violence and freedom from torture and freedom from the threat of fear is a dream of a state law that has been listed in the Constitution of 1945. The principle insaniyah with universal values that do not conflict with Pancasila, it protects the human rights of all individuals or especially relations between men and women. The duty of the state executive, legislative and judicial branches of government as well as all the people of Indonesia to carry out the follow-fulfillment of human rights in accordance with the duties and responsibilities of each.